2015
DOI: 10.4149/bll_2015_060
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and stereological assessment of the effects of zinc oxide nanoparticles on the mouse testicular tissue

Abstract: Objective: To evaluate the effects of zinc oxide nanoparticles (ZNPs) on morphometric and stereological parameters of mouse testis. Background: ZNPs are increasingly used in sunscreens, biosensors, food additives, pigments, rubber manufacture, and electronic materials. However, the potential toxicity of these nanoparticles is not well understood. Methods: Experimental Groups (ZNP-1, ZNP-2 and ZNP-3) received one of the following treatments daily for 35 days: 5, 50 and 300 mg/kg ZNPs respectively. Right testis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…studies (Hong et al, 2015;Khorsandi et al, 2017;Mozaffari, Parivar, Roodbari, & Irani, 2015). Therefore, it is logical to say that the reduction of sperm count and motility, and the alter- Talebi et al (2013), Moridian, Khorsandi, and Talebi (2015) and Khorsandi, Orazizadeh, Mansouri, Hemadi, and Moradi-Gharibvand (2016). important molecule that acts as a substrate for GSH-Px and GST is the GSH (Josephy, Mannervik, & De Montellano, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…studies (Hong et al, 2015;Khorsandi et al, 2017;Mozaffari, Parivar, Roodbari, & Irani, 2015). Therefore, it is logical to say that the reduction of sperm count and motility, and the alter- Talebi et al (2013), Moridian, Khorsandi, and Talebi (2015) and Khorsandi, Orazizadeh, Mansouri, Hemadi, and Moradi-Gharibvand (2016). important molecule that acts as a substrate for GSH-Px and GST is the GSH (Josephy, Mannervik, & De Montellano, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ZnONP-2 and BZnO-2 hurt sexual performance, with a more adverse effect for BZnO-2. This could be attributed to the NPs’ administration at low doses, which might have a defensive impact through their antioxidant processes, while high doses could have a harmful effects [ 30 ]. This was supported by [ 31 ], who reported that ZnONP at a low dose (5 mg/kg) could have a beneficial effects on male reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, both sexes may be affected, whereas in the second one the mother and the concepts may be injured. As far as the first types of effects are concerned, most available evidence is indirect, consisting of organic and functional (i.e., hormone secretion) alterations of the gonads in rodents, reported after exposure to various ENM such as nickel (Kong et al, 2014), gold (Li et al, 2013), carbon black (Yoshida et al, 2009), silver (Castellini et al, 2014), titanium dioxide ENM (Tassinari et al, 2014), and zinc oxide ENM (Moridian, Khorsandi, & Talebi, 2015). For silica ENM and MWCNT, it has been shown that the alterations may be transient, with a return to normal after about 2 months for silica ENM (Xu et al, 2014) and 3 months for MWCNT (Bai et al, 2010).…”
Section: Toxicity To Reproductionmentioning
confidence: 99%